Human-to-human transmission of severe fever with thrombocytopenia syndrome virus through potential ocular exposure to infectious blood - Yong-Xiang Wu; Xin Yang; Yu Leng; Jia-Chen Li; Lan Yuan; Zhen Wang; Xue-Juan Fan; Chun Yuan; Wei Liu; Hao Li (International Journal of Infectious Diseases, 2022)
ABSTRACT: Severe fever with thrombocytopenia syndrome (SFTS), an emerging infectious disease with high mortality, was first reported in 2009 in China and subsequently endemic to South Korea, Japan, Vietnam, and Myanmar. This disease is transmitted predominantly by tick bites and potentially human-to-human. Personal protective equipments (PPEs) have been recommended to prevent SFTS human-to-human transmission, whereas the specific use of PPEs and the effect on viral transmission have rarely been reported. This report identified a family cluster of six patients with SFTS virus (SFTSV) infection. All five secondary patients had been wearing gloves and masks when exposed to the blood of the index patient, but none of them wore goggles or face shields for eye protection. Ocular route was suggested as a highly possible mode for SFTSV transmission through epidemiological, serological, and phylogenetic analysis. Eye protection should be stressed for clinicians when exposed to blood or bloody secretions.